A Legal Framework for Outer Space Activities in Malaysia - Mainura, Tunku Intan (International Journal of Scientific Research and Management (IJSRM), 2018)
One common similarity that Malaysia has between itself and the international space programme[1] is the year 1957. [1] Gibson, R., ‘The history of international space programmes’, (2007) 23 (3) Space Policy 155.